Diagnostic accuracy of serum calprotectin measured by CLIA and EIA in juvenile idiopathic arthritis: a proof-of-concept study - Codes-Méndez, Helena; Magallares-López, Berta; Park, Hye-Sang; Mariscal, Anaís; Juárez, Cándido; Boronat, Susana; Martínez-Martínez, Laura; Corominas, Hector (Frontiers in Pediatrics, 2024)
Objective. C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) are used to assess disease activity in juvenile idiopathic arthritis (JIA). However, because these biomarkers do not always differentiate between active and inactive disease, there is a need for alternative markers such as serum calprotectin (sCal). The main aim of this proof-of-concept study was to assess the diagnostic accuracy of sCal in patients with JIA. Secondary aims were to identify the optimal sCal cut-off levels to define active disease and evaluate the association between these biomarkers and disease activity status. Methods. Serum samples were obtained from 25 pediatric patients with JIA. Serum calprotectin levels were determined by two different assays, the QUANTA FLASH chemiluminescence immunoassay (CLIA) from Inova Diagnostics and the solid-phase enzyme immunoassay (EIA) from Bühlmann Laboratories. Diagnostic accuracy was assessed for sCal CLIA, sCal EIA, CRP, and ESR. The results obtained by the CLIA and EIA methodologies were compared. We also evaluated the association between the individual each biomarkers (sCal CLIA, sCal EIA, CRP, and ESR) and disease activity (according to JADAS-27 criteria and the ACR criteria modified by Anink and colleagues). Results. For both sCal assays (CLIA and EIA), the optimal cut-off level (ROC analysis) was the same (2.3 µg/mL). Serum calprotectin levels measured by CLIA and EIA were strongly correlated with each other (Kendall's tau-b, 0.71; p<0.001). Compared to ESR and CRP, sCal CLIA and EIA were both more accurate (i.e., greater sensitivity) in identifying patients with active disease. By contrast, ESR and CRP were more effective in identifying patients in remission (i.e., better specificity). Conclusion. This proof-of-concept study shows that determination of serum calprotectin levels with CLIA or EIA can accurately identify the presence of active disease in patients with JIA.